The woman in the water - Finch, Charles (Charles B.) (Finch, Charles (Charles B.) Charles Lenox series., 2018)
London, 1850: A young Charles Lenox struggles to make a name for himself as a detective--without a single case. Scotland Yard refuses to take him seriously and his friends deride him for attempting a profession at all. But when an anonymous writer sends a letter to the paper claiming to have committed the perfect crime--and promising to kill again--Lenox is convinced that this is his chance to prove himself. The writer's first victim is a young woman whose body is found in a naval trunk, caught up in the rushes of a small islet in the middle of the Thames. With few clues to go on, Lenox endeavors to solve the crime before another innocent life is lost. When the killer's sights are turned toward those whom Lenox holds most dear, the stakes are raised and Lenox is trapped in a desperate game of cat and mouse.